Characteristics Study Of EFB Briquettes And Its Potential Use As Dual Fuel In CVCC - Abd Rahman, Mohammad Fairuz (Universiti Sains Malaysia, 2018)
As a renewable energy, biomass has potential to replace depletion of fossil fuel for automotive and power generation applications. In this study, empty fruit bunch (EFB) is used as a biomass source to become the producer gas to test into constant volume combustion chamber (CVCC). The limitations of fibrous biomass have low bulk density from 80-100kg/